Pulmonary Thromboendarterectomy in Portugal: Initial Experience - Fragata, J (2020)
Introduction: Surgical treatment for chronic thromboembolic pulmonary hypertension (CTEPH) is challenging. Most Portuguese patients with CTEPH have been referred to foreign institutions for treatment, with significant social and economic costs. To meet this emerging need, the cardiothoracic surgery department of Hospital de Santa Marta, Lisbon, has developed a dedicated program for pulmonary thromboendarterectomy (PTE). We hereby present the results for the first 19 patients treated. Methods: We conducted a retrospective analysis of all 19 patients who underwent PTE at Hospital de Santa Marta between 2008 and April 2019. Results: Since 2008, a total of 19 patients have undergone PTE in our department. The procedure was performed with good outcomes in both survival and functional recovery. At the very beginning of the series two patients died perioperatively, before all the team underwent formal training at the Royal Papworth Hospital, UK, with no early deaths since. Postoperative complications were similar to other published series. During 11 years of follow-up, there were three late deaths, all in patients with residual pulmonary arterial hypertension. At the latest follow-up (October 2019), all surviving patients showed significant functional recovery, all in NYHA class I or II, with only one patient on vasodilator therapy with sildenafil (the first in the series, operated in 2008). Conclusions: PTE is a demanding procedure, in which outcomes are related to volume and accumulated experience, however it can be performed safely and with reproducible results by a properly prepared dedicated team with a well-controlled learning curve. More patients and multidisciplinary experience will be needed to further improve and streamline results.